Peristiwa Tutur Remaja Cadel (Zaki) dalam Melafalkan Fonem /r/ dengan Menggunakan Pendekatan Neurolinguistik - Mhd Johan; Gaguk Rudianto; Yunisa Oktavia (Asosiasi Ide Bahasa Kepri, 2026)
The purpose of this study is to explain and identify respondents' speech disorders in pronouncing the phoneme /r/. To identify the data of this study, the researcher uses theories, namely the theory of Sastra, Caplan, Bonvillian. Meanwhile, for the method of obtaining data, the author uses the listening and speaking method. In this case, the author is actively involved in encouraging respondents to speak and asking respondents to pronounce the words that have been prepared. After the respondents pronounce the words, the researcher begins to record and analyze the available data. To analyze this, the researcher uses the contribution method, using techniques for direct elements, such as techniques, deletion and substitution techniques. After analyzing the data, the author can conclude the results of this study. Of the ten utterances of the phoneme /r/, there are six times the ante penultimate process, then for the penultimate position there are three times, and for the ultima position there are also three times. In pronouncing these words, there are seven substitution events that do not create new meaning or the words spoken have no meaning. Meanwhile, in the word /tartar/ there are two events, namely substitution events and substitution events. In the lesap event, a new meaning was created from /tartar/ to /tahta/. For the words /bakar/ to become /baka/ and /polar/ to /pola/, this event is an obliteration event and this event can create new meaning.